Practical challenges in polylexical metronome synchronisation: inadvertent conditioning of participant responses in two successive experiments on P-centre location - McCabe, Connor Peter (My University, 2020)
A metronome synchronisation paradigm was used to investigate possible interaction between P(erceptual)-centre location and initial mutation in Irish (Gaelic). A pilot study returned promising results in a subset of stimuli. Data later collected using only these stimuli differed from those of the pilot: participants exclusively synchronised metronome beats with the possessive particle preceding main lexical targets. In the pilot task, monosyllables as the minimal target, as opposed to exclusively disyllabic two-word possessive phrases in the modified task, may have focussed participants on these. This conditioning has been reinstated in a third version of the task by preceding target phrases with a dummy monosyllable.
ExLing 2020: 11th International Conference on Experimental Linguistics
PUBLISHED
Athens, Greece
Keywords: Methodology; P-centre; Metronome synchronisation; Irish Linguistics; MORPHOLOGY; Psycholinguistics